CONTENT MARKETING TIKTOK AFFILIATE, ULASAN PELANGGAN DAN LIVE STREAMING: MENINGKATKAN MINAT BELI SKINCARE - Fadilah, Inas (Politeknik Negeri Ambon, 2025)
Introduction: Digital technology has transformed the way consumers select goods, particularly in the beauty industry. TikTok, along with the TikTok Shop feature, has become the primary channel for skincare brands to reach customers through content marketing, affiliate programs, customer reviews, and live streaming. The purpose of this study is to examine the impact of TikTok's content marketing, affiliate programs, and live streaming on consumers' purchasing decisions for skincare products. Methods: This research employs a quantitative approach, a type of research commonly referred to as a survey. Primary data were collected through a questionnaire distributed to students of the Sharia Economics Study Program at Annuqayah University, which was compiled based on research variable indicators. For this study, the probability sampling method was employed to select samples from a hundred respondents.Results: The influence of the three independent variables on the dependent variables was measured simultaneously and partially using multiple linear regression data analysis techniques. Islamic economics students at Annuqayah University have shown an increase in their interest in buying skincare products, thanks to the use of TikTok content affiliates, customer reviews, and live streaming. Additionally, buying interest is significantly influenced by these three independent variables acting simultaneously. Despite the simultaneous influences, the analysis revealed that all three variables collectively accounted for 54.3% of buying interest, while other factors contributed to the remaining 45.7%. Keywords: TikTok affiliate content marketing, customer reviews, live streaming, purchase interest, skincare products.